If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1 = -1 Reorder the terms: 1 + 3x = -1 Solving 1 + 3x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = -1 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = -1 + -1 3x = -1 + -1 Combine like terms: -1 + -1 = -2 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667
| -4[2(x-7)+3]+20= | | 2n=0.5+30 | | r-(-3)=3 | | 4x-2-2x=6x-4 | | 4x^2+17x=15 | | r+3=3 | | r-6=-13 | | 3x-9/4=6 | | 4-r=1 | | 12(2x-1)/6=24 | | f+9=6 | | 5-6p+3p-8= | | 22+4x=3-7+2x | | 3-(6x+9)-10x=1 | | 10-2t+6t=t+22 | | 4(2y+9)+7y=24 | | 5(3x-7)=5 | | 7=-3(5+2q) | | 20=d+16 | | 7(x-5)/3=14 | | 235=pi*10*l | | 3x+5(4x-7)=2-(2x+8) | | 4x-5+2=5 | | 2v+3(8-v)=16 | | x^2-36x+27=0 | | x-4/6=4 | | -8n-33=-8-4(2n+6) | | -2+6-s-4= | | 3(x-3)/2=18 | | x+(-3)=100 | | 5x=9x+20 | | 4x^2+16x-28=0 |